Optical Character Recognition Menggunakan Jaringan Syaraf Tiruan dengan Algoritma Perseptron - Rambe, Gusni Sari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of technology today has greatly influenced the development of science, one of which is in the recognition of letter, number and character patterns (pattern recognition). The problem that arises is that each character in the computer or the result of a pattern scan entered into the computer must have a different character pattern recognition, this results in limited human ability to clarify or describe a pattern based on quantitative measurements of the main features or properties of a pattern of letters, numbers and characters. To overcome existing problems, Artificial Neural Networks (ANN) are a tool for solving problems, especially in areas involving grouping and pattern recognition, in general, Artificial Neural Networks have a system that is able to think, consider the actions to be taken, and make decisions like humans. Through the process of character pattern recognition using the Perceptron algorithm, it is hoped that in the future this character recognition system can have a major impact on character recognition that is not in the computer and can make it easier for users to recognize characters and it is also hoped that this algorithm can be used for other objects that will be pattern recognition.